A Common Deletion in the APOBEC3 Genes and Breast Cancer Risk - Long, Jirong; Delahanty, Ryan J.; Li, Guoliang; Gao, Yu-Tang; Lu, Wei; Cai, Qiuyin; Xiang, Yong-Bing; Li, Chun; Ji, Bu-Tian; Zheng, Ying; Ali, Simak; Shu, Xiao-Ou; et al. (JNCI : Journal of the National Cancer Institute, 2013)
Genome-wide association studies (GWASs) have identified multiple genetic susceptibility loci for breast cancer. However, these loci explain only a small fraction of the heritability. Very few studies have evaluated copy number variation (CNV), another important source of human genetic variation, in relation to breast cancer risk. We conducted a CNV GWAS in 2623 breast cancer patients and 1946 control subjects using data from Affymetrix SNP Array 6.0 (stage 1). We then replicated the most promising CNV using real-time quantitative polymerase chain reaction (qPCR) in an independent set of 4254 case patients and 4387 control subjects (stage 2). All subjects were recruited from population-based studies conducted among Chinese women in Shanghai. Of the 268 common CNVs (minor allele frequency ≥ 5%) investigated in stage 1, the strongest association was found for a common deletion in the APOBEC3 genes (P = 1.1×10(-4)) and was replicated in stage 2 (odds ratio =1.35, 95% confidence interval [CI] = 1.27 to 1.44; P = 9.6×10(-22)). Analyses of all samples from both stages using qPCR data produced odds ratios of 1.31 (95% CI = 1.21 to 1.42) for a one-copy deletion and 1.76 (95% CI = 1.57 to 1.97) for a two-copy deletion (P = 2.0×10(-24)). We provide convincing evidence for a novel breast cancer locus at the APOBEC3 genes. This CNV is one of the strongest common genetic risk variants identified so far for breast cancer.